Newspaper and internet display advertising: Co-existence or substitution? - Nadine Lindstädt; Oliver Budzinski (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2012)
Newspapers have been experiencing declining circulation figures and diminishing advertising revenues for several years - both effects might pose a threat to the continuing existence of (print) newspapers. In an earlier paper, Lindstädt & Budzinski (2011) argued from a theoretical viewpoint that industry-specific patterns exist that determine substitution or complementation effects between internet and newspaper advertising. It was argued that retail advertising, in particular, may offer a niche for regional/local newspapers that can be expected to present a sustainable segment of complementarity along with the otherwise mostly substitutional advertising markets. This paper empirically tests these hypotheses by analyzing advertising spending data for newspaper and internet display advertising of 13 different industries in the U.S. from 2001-2010. We find evidence for some of the hypotheses. Whereas some industries showed clear substitution effects between internet display and newspaper advertising, the majority of our hypotheses could be only partly rejected: newspaper substitution effects could be observed, however, in the direction to traditional media platforms instead of internet display advertising. For two retail-sub-industries, the hypotheses could not be rejected for the analyzed period.
Keywords: L82; A20; L13; M21; 330; media economics; advertising; complementation; substitution; newspapers; internet; Werbeträger; Zeitungswerbung; Online-Marketing; Vertriebsweg; Branche; USA